PENGARUH KEGIATAN PLANTING IN POTS TERHADAP LITERASI SAINS ANAK USIA 4-5 TAHUN - Ferreira Mulya Fasha; Mallevi Agustin Ningrum; Eka Cahya Maulidiyah; Kartika Rinakit Adhe (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the effect of planting in pots activities on the scientific literacy of children aged 4-5 years in Smart School Kindergarten. The approach used is a quantitative method with a pre-experimental design. Pre-experimental uses a one group pretest-posttest model. The subjects of this study consisted of 17 children in group A. Data collection techniques used were observation, interviews, and documentation. Data analysis techniques used the Wilcoxon signed-rank test. Based on the results of the data analysis, the Z value was obtained at -3.741b with an Asymp, Sig. (2-tailed) value of 0.000. The significance value is smaller than the specified significance level of 0.05 (0.000 <0.05). So, it can be concluded that there is an effect of planting in pots activities on the scientific literacy of children aged 4-5 years in Smart School Kindergarten.